Learner Perceptions of Electronic End‐of‐shift Evaluations on An Emergency Medicine Clerkship. Issue 1 (17th April 2020) - Nable, Jose V.; Bhat, Rahul; Isserman, Jacob; Smereck, Janet; Wilson, Matthew; Maloy, Kevin
Abstract: Objectives: As students on an emergency medicine (EM) rotation work with different faculty on a daily basis, EM clerkships often incorporate an end‐of‐shift evaluation to capture sufficient student performance data. Electronic shift evaluations have been shown to increase faculty completion compliance. This study aimed to examine learner perceptions of their individualized feedback during an EM clerkship following the adoption of an electronic evaluation tool. Methods: This retrospective study examined end‐of‐rotation surveys that students complete at the conclusion of their EM rotation. Survey respondents used a standard Likert scale (1–5). This study examined responses to the question: "The feedback I received on this rotation was adequate." The study period included the 3 academic years prior to and subsequent to the adoption of an electronic evaluation system (replacing paper end‐of‐shift evaluations). The primary outcome was the mean Likert score and the secondary outcome was the percentage of students who rated their feedback a "5" or "strongly agree." Results: A total of 491 students responded (83.9% response rate) to the survey during the paper evaluation period, while 427 responded (80.7% response rate) in the electronic period. The mean response improved from 4.02 (paper evaluations) to 4.22 (electronic evaluations; mean difference = 0.20, p < 0.05). The percentage of students who responded with a 5 improved (31% with paper evaluations vs. 41% with electronic evaluations, p < 0.05). Conclusions: The adoption of an electronic end‐of‐shift evaluation system was associated with improved learner perception of their feedback as compared to paper evaluations. Electronic evaluations are a useful tool to gather just‐in‐time data on learner performance.